Penguatan Community Mental Health Nursing (CMHN) - Desty Ratna Purwaningsih; Diva Aryanti; Zayyantri Ghinadha Setyawati; Moh Hanafi; Angga Sugiarto (Universitas Sebelas Maret, 2024)
The Community Mental Health Nursing (CMHN) program is part of a community-based public health initiative. CMHN is implemented in Paingan, Trasan, Bandongan, Magelang. This program aims to improve the mental and physical well-being of residents, with a focus on strengthening CMHN in early detection and management of mental health disorders. The areas of service include promotive, preventive, curative, and rehabilitative efforts. The main challenge in implementing the program lies in the motivation of CMHN volunteers in carrying out activities. After training and mentoring, the volunteers' performance improved, particularly in terms of intervention and support. Continuous training and motivation are essential to optimize the role of CMHN volunteers in supporting community mental health